ANALYSIS OF ISLAMIC EDUCATION POLICY AND PROBLEMS - Ahmad Taufiki; Fathor Rozi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Education is a key pillar in human resource development in Indonesia. However, the quality of education still faces various challenges, such as unequal access and low teaching quality. This study aims to analyze the education policies implemented by the government to improve the quality of education in Indonesia. Using a qualitative approach, the policy analysis was conducted to identify factors influencing the effectiveness of the policies and their impact on society. The analysis shows that despite the existence of programs such as compulsory education and teacher competency improvement, the gap between formulated policies and their implementation remains a major problem. Therefore, a more inclusive and participatory approach to education policy formulation is needed to ensure that each policy adopted addresses local needs and improves the overall quality of education. Islamic education in Indonesia faces a number of complex and diverse problems. This article uses a qualitative research approach to gain a deeper understanding of these issues. Through literature review, stakeholder interviews, and participant observation in Islamic education settings, this study uncovers key challenges, including the quality gap between formal and non-formal Islamic education, the lack of harmonization between Islamic education and the national education system, the need to improve the competency of educators, and the challenges of technology and globalization.